Allogeneic apoptotic thymocyte-stimulated dendritic cells expand functional regulatory T cells - da Costa, Thaís Boccia (Blackwell Science Inc, 2011)
Dendritic cells (DCs) play an important role in the clearance of apoptotic cells. The removal of apoptotic cells leads to peripheral tolerance, although their role is still not clear. We show that the uptake of apoptotic thymocytes by DCs converts these cells into tolerogenic DCs resistant to maturation by lipopolysaccharide, modulating the production of interleukin-12 and up-regulating the expression of transforming growth factor-β(1) latency associated peptide. We also observed that DCs pulsed with apoptotic cells in the allogeneic context were more efficient in the expansion of regulatory T cells (Tregs), and that this expansion requires contact between DCs and the T cell. The Tregs sorted from in vitro culture suppressed the proliferation of splenocytes in vitro in a specific and non-specific manner. In the in vivo model, the transfer of CD4(+) CD25(−) cells to Nude mice induced autoimmunity, with cell infiltrate found in the stomach, colon, liver and kidneys. The co-transfer of CD4(+) CD25(−) and CD4(+) CD25(+) prevented the presence of cell infiltrates in several organs and increased the total cell count in lymph nodes. Our data indicate that apoptotic cells have an important role in peripheral tolerance via induction of tolerogenic DCs and CD4(+) CD25(+) Foxp3(+) cells that present regulatory functions.